Determinan Minat Menggunakan Uang Elektronik Pada Aplikasi Shopeepay : Sebuah Persepektif Technology Accepyance Model (TAM) - Kharisma Nugraha Putra; Merisa Oktaria; Astia Putriana (FKIP, Universitas Palangka Raya, 2022)
This research adopted the Technology Acceptance Model to examine the factors affecting the intentions to use electronic money on digital application shopeepay. The purpose of this research are to examine the effect of perceived ease of use and perceived usefulness on the intentions to use electronic money on digital application shopeepay. The sample in this study were undergraduate students of the economic education study program at the University of Palangka Raya who were active in the even semester of the 2021/2022 academic year. The method of data collection is survey using questionnary as instrument of the research. The ammount of the sample was 70. The data was analysed using Structural Equation Modelling- Partial least square (SEM-PLS) with SmartPLS 3.0. The result of research finds perceived ease of use and perceived usefulness has a positive effect on the intentions to use electronic money on digital application shopeepay.